Government mandatory energy-biased technological progress and enterprises' environmental performance: Evidence from a quasi-natural experiment of cleaner production standards in China - Li, Zhen; Wu, Baijun; Wang, Danyang; Tang, Maogang (Energy policy, 2022)
The effective government mandatory energy-biased technological progress and its transition to price-induced or R&D-induced technological progress is critical to achieving sustainable development in developing countries such as China. Based on a quasi-natural experiment of cleaner production standards in China, this study investigated the impact of government mandatory energy-biased technological progress on enterprises' environmental performance using the difference-in-differences method. Highly robust benchmark results indicated that the implementation of cleaner production standards effectively reduced the SO2 emissions intensity of enterprises, but failed to reduce the aggregate SO2 emissions. Mechanism analysis showed that the SO2 emissions intensity reduction effect is achieved by introducing advanced production process and desulfurization equipment and thus increasing fixed investment. Nevertheless, it “squeezes out” enterprises' R&D expenditures and increases the amount of coal consumption. Moreover, it can improve the degree of resource misallocation through affecting the entry and exit decisions of companies with heterogeneous productivity. Heterogeneity analysis revealed that the implementation of cleaner production standards is affected by enterprise ownership, industry characteristics, etc. This study suggests that the government should develop a market-oriented energy price regime, optimize the energy factor market, and improve the dual control system of energy consumption intensity and aggregate energy consumption. •Effect of government mandatory energy-biased technological progress on enterprises' environmental performance was evaluated.•Results showed reduced SO2 emissions intensity of enterprises but not the aggregate emissions.•Operational strategies of enterprises promoted environmental performance.•Energy resource misallocation improved via enterprises' entry and exit decisions.